2019
DOI: 10.3904/kjim.2018.054
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin resistance and female gender affect Helicobacter pylori eradication failure in chronic gastritis

Abstract: Clarithromycin resistance and female gender are factors affecting H. pylori eradication failure in patients with chronic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
5
25
1
Order By: Relevance
“…In this study, there was no signi cant correlation between age and sex of the patients with clarithromycin resistance. This is in line with the results of Korona [41] and Elviss [42] and contrasts with the results of Wang [36], Chang [43], and Treiber [32]. In this study, a signi cant relationship was observed between the degree of chronic in ammation and Glandular Atrophy with antibiotic resistance.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, there was no signi cant correlation between age and sex of the patients with clarithromycin resistance. This is in line with the results of Korona [41] and Elviss [42] and contrasts with the results of Wang [36], Chang [43], and Treiber [32]. In this study, a signi cant relationship was observed between the degree of chronic in ammation and Glandular Atrophy with antibiotic resistance.…”
Section: Discussionsupporting
confidence: 81%
“…In all studies included, 11 prospective studies compared the H. pylori eradication rate in diabetes and non‐diabetes 29‐39 . Eleven retrospective studies compared the proportion of diabetes and other clinic factors (age, gender, smoking, drinking, overweight, peptic ulcer disease, blood pressure, and history of NSAIDS) in groups failed and succeed in H. pylori eradication 40‐50 . Four studies further compared the level of HbA1c in diabetics failed and succeed in H. pylori eradication 30,35,37,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies were included in these part of meta‐analysis, included 11 case‐control studies 29‐39 and 11 cohort studies 40‐50 enrolling in 5466 participants. Among them, three studies were split into two part to be included, 33,36,48 according to their group design.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 One study showed that female gender (OR, 1.73; 95% CI, 1.15 to 4.25) and clarithromycin resistance (OR, 19.13; 95% CI, 9.35 to 35.09) were strongly associated with eradication failure. 35 Another study also showed that female gender and smoking were associated with the treatment failure. 36 The reason may be also related to clarithromycin resistance and point mutation.…”
Section: Discussionmentioning
confidence: 99%